(untitled) (Jurnal Manajemen Bisnis, 2023)
The point of this study is to try and look into what happens to employee productivity at PT. Infomedia (Grahapena) Makassar when they get education and training to improve their performance. This study’s group was made up of up to 60 people who worked at PT. Infomedia (Grahapena). In this study, a saturated sampling method was used to choose the sample, which meant that the whole community was used as the research sample. This study used first-hand information as its data source. A questionnaire filled out by PT workers was used to get primary data for this study. The news agency GRAhapena in Makassar. There are different types of tests used to look at data, such as validity tests, reliability tests, multiple linear regression analysis, partial tests, simultaneous tests, determination tests, and classical assumption tests (such as normality tests, heteroscedasticity tests, and multicollinearity tests). The study shows that training makes PT workers more productive, and the effect is big and positive. The news agency GRAhapena in Makassar. This means that training is a factor in figuring out how productive an employee is at work. On the other hand, schooling doesn’t have a big effect on how much work people get done. This means that schooling is not a factor that affects how well employees do their jobs at PT. Infomedia (Graha Pena) Makassar.